2016
DOI: 10.1111/ecog.02010
|View full text |Cite
|
Sign up to set email alerts
|

Plants show more flesh in the tropics: variation in fruit type along latitudinal and climatic gradients

Abstract: Fruit type has a major impact on seed dispersal, seed predation and energy allocation, but our understanding of large‐scale patterns in fruit type variation is weak. We used a dataset of 4008 Australian species to provide the first continental‐scale tests of a series of hypotheses about the factors that might affect fruit type. We found a significant latitudinal gradient in the proportion of fleshy‐fruited species, with the percentage of fleshy‐fruited species rising from 19% at 43.75°S to 49% at 9.25°S. Speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
83
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(98 citation statements)
references
References 67 publications
12
83
2
Order By: Relevance
“…The elevational ranges are from 600 to 6,000 m F I G U R E 4 The relationship between spinescence and herbivorous mammal richness for every 100 m belt in the Qinghai-Tibetan Plateau. Thus, our analyses consider the proportion of spinescent species in elevational belts that are appropriately weighted according to the number of species they contain (Chen et al, 2017), which means that a belt with 400 species gets more weight than does a belt with fewer than 40 species. The fitted lines display the predicted probabilities of spinescent species as fit by logistic regression models life-form.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The elevational ranges are from 600 to 6,000 m F I G U R E 4 The relationship between spinescence and herbivorous mammal richness for every 100 m belt in the Qinghai-Tibetan Plateau. Thus, our analyses consider the proportion of spinescent species in elevational belts that are appropriately weighted according to the number of species they contain (Chen et al, 2017), which means that a belt with 400 species gets more weight than does a belt with fewer than 40 species. The fitted lines display the predicted probabilities of spinescent species as fit by logistic regression models life-form.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…frugivorous birds divide the niche of fruiting plants most finely at high latitudes where they also form modular subsets of closely associated plant and bird species (Fig. We note that temperate biomes are also characterized by having less plant species with fleshy fruits than tropical biomes (Chen et al 2016) and that previous studies have shown There is an opposed latitudinal pattern of network-derived and assemblage-level dietary specialization: (a) the proportion of obligate frugivorous birds decreases with latitude, whereas network-derived (b) complementary specialization (∆-VA H 2 ′) and (c) modularity (∆-VA Q) increased with latitude. At the same time, however, there are more obligate frugivorous bird species in the tropics than in temperate regions, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this gradient at landscape scale on Réunion is greater than the one shown at continental scale by Chen et al. (). The sharp decrease of pFF with elevation on Réunion shows how important the last remaining vegetation corridors along environmental gradients are in understanding biodiversity patterns.…”
Section: Discussionmentioning
confidence: 57%
“…In the lowlands, woody plants are more likely to bear fleshy fruits on the windward side where there is no dry season. The positive, linear influence of precipitation on pFF has already been shown for mainland worldwide (Almeida‐Neto et al., ; Chen et al., ; Correa et al., ) and Madagascar (Bollen et al., ). Lower pFF on the leeward may be the consequence of higher water requirements for making fleshy diaspores.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation